Peran United Nations Children’s Fund (Unicef) dalam Peningkatan Kualitas Pendidikan di Papua Tahun 2020-2021 - Indriani, Winda (Jurnal Sosial-Politika, 2024)
This research aim to identify and describe the role of international organization United Nations Children's Fund (UNICEF) in improving the quality of education in Papua in 2020-2021. The research used a descriptive method with secondary data, was collected through literature such as journals, documents and the internet, and used qualitative data analysis techniques. This research used the theory of the role of international organizations from Clive Archer to explain the research questions. The results of this research, the condition of education in Papua is a complex problem, which is related to various factors that make education very lagging. Starting from high poverty levels, uneven implementation of the curriculum, limited teachers, limited schools, diverse socio-cultures, relatively high illiteracy rates, lack of enrollment of the population who are currently in school and increasing dropout rates, this situation makes the Human Development Index (HDI) low. Efforts have been made by the local government, but there are still challenges in improving the quality of education in Papua. As an international organization that focuses on the protection and welfare of children around the world, UNICEF performs its role as an international organizational actor by running the rural and remote education initiative for Papuan Provinces.